Estimation of the pore water pressure and the settlement of saturated clay subjected to undrained multi-directional cyclic shear by using hypecbolic function in combination with the “curve-fitting” method - Nhan, Tran Thanh; Tuyen, Tran Huu; Thien, Do Quang; Yen, Nguyen Thi Ngoc (Vietnam Journal of Earth Sciences, 2015)
In this research, saturated-normally consolidated samples of kaolinite clay were tested under undrained uni-directional and multi-directional cyclic simple shears with various shear strain amplitude (g), cyclic shear direction and consolidation pressure (sv0). It is indicated from experiment results that cyclic shear direction and shear strain amplitude have important effect on the pore water pressure accumulation during undrained cyclic shear and the recompression characteristics after cyclic shear, meanwhile the effect of consolidation pressure on these properties, at least in the range from 49 kPa to 98 kPa, is negligible. The pore water pressure induced by multi-directional cyclic shear can be estimated by using hyperbolic function of shear strain amplitude and the number of cycles in combination with the “curve-fitting” technique. However, the obtained results for the case of multi-directional cyclic shear is not so good as those for the uni-directional one, especially in the range of g = 0.3% ~ 0.8%. On the other hand, the conventional estimation method of post-cyclic settlement can be used in combination with different compression indices for predicting the settlement of saturated clay layer subjected to undrained multi-directional cyclic shear.ReferencesMatsuda H, 1997: Estimation of post-earthquake settlement-time relations of clay layers, Journal of JSCE Division C, JSCE; 568(III-39), 41-48 (in Japanese). Matsuda H, Shinozaki H, Okada N, Takamiya K, Shinyama K, 2004: Effects of multi-directional cyclic shear on the post-earthquake settlement of ground, Proc. of 13th World Conf. on Earthquake Engineering; No. 2890. Tokimatsu  K,  Katsumata  K,  2011:  Liquefaction-induced damage  to  buildings  in  Urayasu  city  during  the 2011 Tohoku  Pacific earthquake,  Proc.  Int.  Symp.  On Engineering  lessons  learned  from  the  2011  Great  East Japan Earthquake, 665-674. Lessons, 2012: Learned from the 2011 Great East Japan Earthquake, 665-674. Ansal A, Iyisan R, Yildirim H, 2001: The cyclic behavior of soils and effects of geotechnical factors in microzonation, Soil Dynamics and Earthquake Engineering, Vol.21, No.5, 445-452. S. Ohara, H. Matsuda, Y. Kondo, 1984: Cyclic simple shear tests on saturated clay with drainage, Journal of JSCE Division C, JSCE, Vol. (352/III-2), 149-158 (in Japanese). S. Ohara, H. Matsuda, 1988: Study on the settlement of saturated clay layer induced by cyclic shear, Soils and Foundations, Vol. 28, No. 3, 103-113. N. Matasovic, M. Vucetic, 1995: Generalized cyclic degradation pore pressure generation model for clays, J. Geotechnical Eng., ASCE, Vol. 121, No. 1, 33-42. JGS, 2000: Soil test procedure and explanation (in Japanese). Yasuhara K, 1995: Consolidation and settlement under cyclic loading, Proc. Int. Symp. on Compression and Consolidation of Clayey Soils, 979-1001. Yasuhara K, 1991: Andersen KH. Recompression of normally consolidated clay after cyclic loading, Soils and Foundations, 31(1): 83-94. H. Matsuda, H. Nagira, 2000: Decrease in effective stress and reconsolidation of saturated clay induced by cyclic shear, Journal of JSCE Division C, JSCE, Vol. 659(III-52), 63-75 (in Japanese). K. Yasuhara, S. Murakami, N. Toyota, A. F. L. Hyde, 2001: Settlements in fine-grained soils under cyclic loading, Soils and Foundations, Vol. 41, No. 6, 25-36. Matsuda H, Ohara S, 1989: Threshold strain of clay for pore pressure buildup, Proc. of 12h World Conf. on Soil Mechanics and Foundation Engineering, Rio De Janeiro, 127-130.